Accuracy of Electronic Devices Efficiency Evaluation - Eidukas, D.; Stupak, V. (Elektronika ir Elektrotechnika, 2011)
Electronic devices are considered. In an interval between inspections periodic controls of serviceability are stipulated. The method of definition of accuracy of evaluation of efficiency index of devices is offered. Accuracy is characterized by an error caused by likelihood properties of parameters, influencing an index of efficiency. Error is defined by means of the computing experiment based on a method of statistical modeling. During experiment, 1000 realizations are received. Parameters influencing an index of efficiency are presented by random variables distributed under the rectangular law. Data of computing experiment show that half of width of confidential intervals 99 percent for an index of efficiency does not exceed 0.05 % (of size of a sample mean). Values of factor of variation do not exceed 0.60 %, and the error of evaluation of efficiency index does not exceed 1.80 % (of size of a sample mean). Ill. 1, bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.355